2008
DOI: 10.1074/jbc.m708811200
|View full text |Cite
|
Sign up to set email alerts
|

Tor Pathway Control of the Nitrogen-responsive DAL5 Gene Bifurcates at the Level of Gln3 and Gat1 Regulation in Saccharomyces cerevisiae

Abstract: The Tor1,2 protein kinases globally influence many cellular processes including nitrogen-responsive gene expression that correlates with intracellular localization of GATA transcription activators Gln3 and Gat1/Nil1. Gln3-Myc 13 and Gat1-Myc 13 are restricted to the cytoplasm of cells provided with good nitrogen sources, e.g. glutamine. Following the addition of the Tor1,2 inhibitor, rapamycin, both transcription factors relocate to the nucleus. Gln3-Myc 13 localization is highly dependent upon Ure2 and type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
149
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(168 citation statements)
references
References 49 publications
18
149
1
Order By: Relevance
“…In case of S. cerevisiae, the TOR pathway is involved in the intracellular localization of the GATA-type TFs, Gln3 and Gat1, in response to the nitrogen status as mentioned in Introduction (6)(7)(8). Recently, it was revealed that the TOR pathway also plays an important regulatory role in NCR sensitive transcription even after Gln3 is localized to the nucleus (27). Given the conserved structure and functions of TOR kinase among eukaryotes, it would be natural to postulate that the TOR pathway also plays a central role in the regulation of nitrogen assimilation genes through modification of the R2R3-type MYB TFs in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…In case of S. cerevisiae, the TOR pathway is involved in the intracellular localization of the GATA-type TFs, Gln3 and Gat1, in response to the nitrogen status as mentioned in Introduction (6)(7)(8). Recently, it was revealed that the TOR pathway also plays an important regulatory role in NCR sensitive transcription even after Gln3 is localized to the nucleus (27). Given the conserved structure and functions of TOR kinase among eukaryotes, it would be natural to postulate that the TOR pathway also plays a central role in the regulation of nitrogen assimilation genes through modification of the R2R3-type MYB TFs in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…6, A and B, ure2⌬ Gln, of Ref. 48), whereas Gat1-Myc 13 similarly relocates in less than 1 ⁄ 3 of them and remains exclusively cytoplasmic in almost half of them (Fig. 6, C and D, ure2⌬ Gln, of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Work to this point has provided a detailed view of conditions and phosphatase requirements affecting the intracellular localization of Gln3-Myc 13 . Unfortunately, similar information for Gat1 was lacking except for the observations that rapamycin treatment did not demonstrably affect the electrophoretic mobility of Gat1-Myc 13 (44), and rapamycin-induced nuclear Gat1-Myc 13 localization occurred similarly in wild type and sit4⌬ cells (48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin treatment also triggers nuclear import of Gat1 (Beck et al 1999). How TORC1 regulates this process is unclear, yet it appears to be different from TORC1-dependent Gln3 control and does not involve Ure2 or Sit4 (Kuruvilla et al 2001;Crespo et al 2002;Georis et al 2008).…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 98%